2016
DOI: 10.1177/0954405416640416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting edge modification on the tool flank wear in ultrasonically assisted turning of hardened steel

Abstract: Ultrasonically assisted turning is one of the modern machining processes developed in recent decades to facilitate machining of hard-to-cut materials which are widely used in different industries. Cutting tool wear is one of the main problems in machining of hard materials which has necessitated implementation of modern machining processes such as ultrasonically assisted turning. Due to vibro-impact conditions, cutting tool failure takes place when ultrasonically assisted turning is applied for hard and brittl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The intermittent cutting of UAT reduced the tool contact time with the chip, reducing the heat conduction to the chip's tool face due to the chip's lower tool wear than CT. The authors found that applying vibration improved the surface finish compared to CT. Farahnakian et al 15 studied the flank wear of the WC tool with and without initial wear when machining the hardened alloy steel. The authors found that modified WC tools produced less flank wear than CT and UAT with ordinary carbide tools at cutting speeds well below the critical cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent cutting of UAT reduced the tool contact time with the chip, reducing the heat conduction to the chip's tool face due to the chip's lower tool wear than CT. The authors found that applying vibration improved the surface finish compared to CT. Farahnakian et al 15 studied the flank wear of the WC tool with and without initial wear when machining the hardened alloy steel. The authors found that modified WC tools produced less flank wear than CT and UAT with ordinary carbide tools at cutting speeds well below the critical cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…Related experiments resulted in patterns of dimple array and proved the performance of the presented process. Farahnakian et al 15 studied the surface roughness during the one-directional ultrasonic assisted turning. They presented a special tool with a modified cutting edge with a flexible fabrication process which resulted in various types of textures on machined surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Different traditional and modern techniques are nominated to enhance surface quality of the workpiece according to cost, time, workpiece material, and surface complexities demands. In recent decades, the vibration of a tool or workpiece is known as an efficient assistant technique in conventional [1][2][3][4][5][6][7][8][9][10][11][12][13] and non-conventional [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] machining processes. Vibratory and ultrasonic machining are two main non-conventional polishing processes, which are based on vibration phenomenon.…”
Section: Introductionmentioning
confidence: 99%